Surveillance of Culicine Mosquitoes in Six Villages of Taita-Taveta County, Kenya, With Host Determinations From Blood-Fed Females. Issue 6 (13th June 2020) - Munyao, Vanessa; Karisa, Jonathan; Munyao, Carol Munini; Ngari, Moses; Menza, Nelson; Peshu, Norbert; Rono, Martin; Mbogo, Charles; Mwangangi, Joseph
Abstract: Culicine mosquitoes are vectors of human disease-causing pathogens like filarial worms and several arthropod-borne viruses (arboviruses). Currently, there has been an increase in emerging and re-emerging vector-borne diseases along coastal Kenya, which has been of major concern in public health. This study aimed at determining culicine mosquito species abundance, diversity and their host feeding preferences in Taita-Taveta County, Coastal Kenya. Entomological sampling was done during the long-wet season (March and May) and long dry season (June to October) 2016–2018. Mosquito sampling was done using CDC light traps and Backpack aspiration for indoor and outdoor environments. All culicine mosquitoes collected were identified morphologically and categorized according to their physiological status. Blood fed culicine mosquitoes were tested for bloodmeal sources using ELISA. In total, 3, 278 culicine mosquitoes were collected, of which 738 (22.5 %) were found indoors and 2, 540, (77.5 %) outdoors. The mosquitoes consisted of 18 species belonging to four genera: Aedes (7), Culex (8), Mansonia (2), and Coquillettidia (1). Overall, there was high mosquito species diversity ( H ) in outdoors ( H = 2.4339) than in indoors ( H = 2.2523), whereas even distribution ( EH ) was higher in indoors ( EH = 0.9064) than outdoors ( EH = 0.8266). Majorly the bloodmeals identified were from multiple host sources with (51.6%), single hosts (41.3%), and unidentified (7.2%). This study has demonstrated a high diversity of culicine mosquitoes with relaxed feeding tendencies. These mosquitoes are contributing to mosquito biting nuisance and the likelihood of exposure of populations to diseases of public health. Graphical Abstract: